Synergetic Effects of Soil Organic Matter Components During Interactions with Minerals - Qafoku, Odeta; Andersen, Amity; Zhao, Qian; Mergelsberg, Sebastian T; Kew, William R; Eder, Elizabeth K; Resch, Charles T; Graham, Emily B; Qafoku, Nikolla P (Environmental science & technology, 2024)
Mineral-associated soil organic matter (SOM) is critical for stabilizing organic carbon and mitigating climate change. However, mineral-SOM interactions at the molecular scale, particularly synergetic adsorption through organic-organic interaction on the mineral surface known as organic multilayering, remain poorly understood. This study investigates the impact of organic multilayering on mineral-SOM interactions, by integrating macroscale experiments and molecular-scale simulations that assess the individual and sequential adsorption of major SOM compounds-lauric acid (lipid), pentaglycine (amino acid), trehalose (carbohydrate), and lignin onto soil minerals. Ferrihydrite, Al-hydroxide, and calcite are exposed to SOM compounds to determine adsorption affinities and binding energies. Results show that lauric acid has 20-40 times higher than pentaglycine, following the order (ferrihydrite) > (Al-hydroxide) ≫ (calcite). Molecular-scale simulations confirm that lauric acid has a higher binding energy (30.8 kcal/mol) on ferrihydrite than pentaglycine (6.0 kcal/mol), attributed to lipid hydrophobicity. The lower binding energy of pentaglycine results from its hydrophilic amide groups, facilitating partitioning into water. Sequential experiments examine how the first layer of lipid or amino acid affects the adsorption of carbohydrate/lignin, which show little or no individual adsorption affinities. Macroscale results reveal that lipid and amino acid adsorption induce ferrihydrite particle repulsion increasing reactive surface area and enhancing carbohydrate/lignin adsorption independently and synergistically through organic multilayering. Molecular-scale results reveal that amino acid adsorbed on ferrihydrite interacts more readily with lignin macroaggregates (preformed in solution) than with individual lignin units, indicating organic multilayering via H-bonding. These findings reveal the molecular mechanisms of SOM-mineral interactions, crucial for enhancing soil carbon stabilization.